If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -10 + -4x = -25 Reorder the terms: -10 + x + -4x = -25 Combine like terms: x + -4x = -3x -10 + -3x = -25 Solving -10 + -3x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -3x = -25 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = -25 + 10 -3x = -25 + 10 Combine like terms: -25 + 10 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 3+10+5y=20 | | 3x=2+1 | | 72=2+3a+2a | | 9x+x=9 | | 12x+3=2x+1 | | y+7x=16 | | 3(-25-6+8)= | | -9+5x+x=63 | | 2x+41+127=180 | | 7a-28b/a-4b | | 4(3x+2)(3x+2)=5 | | 46=3w^2+3w | | 5x5/7 | | 6x^2+12x-16=20 | | 15*m=42 | | 2x*2x+2x-12=0 | | -6(v+3)+3v+6=6v+8 | | 54x^2+48x+11=0 | | 315/x=4/16 | | .5x=1.56 | | 6+10x=-94 | | 2[7-6(1-n)]+9=-32+6[6(n+1)-3n] | | 2/7b=1/7 | | 0=2y-3 | | 2sin^2(x)-sin(x)-1=0 | | 4n+16=56 | | X^4+6x-108=0 | | 1/3y≥5 | | .3x-5.04=-6.3 | | f(f(x))=25x+9 | | H(t)=-16t^2+72t+5 | | 4/3(pi)10^3 |